TEACHERS™ USE OF TELEGRAM CHATBOT AS LEARNING MEDIA AT SMPN 4 BINJAI - HASIBUAM, JULI RACHMADANI; AS, MANSUR; NASUTION, NAZLAH SYAHAF; KASIH, INDRA; HARAHAP, MAZAYA ZAHIRA (Universitas Negeri Medan, 2024)
This study explores the implementation of Telegram chatbots as learning media at SMPN 4 Binjai, focusing on enhancing teaching and learning processes through digital transformation. Telegram can serve as effective learning tools by facilitating interaction among teachers, students, and parents (Sanaky, 2023), the research involved training and mentoring 21 teachers using methods such as presentations, discussions, and simulations over three meetings. The chatbots aimed to address challenges such as workload management and student engagement by providing automated content distribution, quizzes, and feedback. Findings indicate that Telegram chatbots significantly enhance the efficiency of delivering educational material, boost student interest and engagement, and promote independent learning. This study underscores the importance of digital literacy in modern education and suggests that ongoing training and support are crucial for maximizing the effectiveness of Telegram chatbots. By creating more interactive and responsive learning environments, chatbots offer a promising future for educational settings. The results highlight the necessity for educational institutions to embrace technological changes and provide continuous training for educators to fully utilize digital tools' potential, thereby improving the overall quality of education.